Peningkatan Motivasi Belajar Siswa melalui Strategi Gubah Lagu - Elfa Tsuroyya (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2017)
Abstract This research aims to find out how to increase student motivation to learn the SKI lesson. In addition, this research will also reveal the extent of student’s learning motivation affect achievement of students. This research is a classroom action research, which has four phases, namely: planning, implementation, observation and reflection. The sample used in this study is the students of class XII-IPA 1 MAN Yogyakarta III. In this classroom action research the researcher uses a strategy of